Smart Budgeting for Future-Ready Schools: Strategies for Efficiency and Financial Accountability in Education Funding - Hamini; Mulawarman, Widyatmike Gede; Haryaka, Usfandi (Journal of Pedagogy and Education Science, 2025)
The increasing demands for quality education amidst budget constraints make the efficiency and transparency of school fund management a crucial issue, especially for Islamic educational institutions. This study aims to formulate a smart budgeting model that not only emphasizes effectiveness and accountability but also integrates Islamic values ​​such as amanah (trust), muʿāwamah (cooperation), and shirkah (partnership). This study employs a qualitative approach, utilizing a literature review method based on secondary sources, including academic journals, educational regulations, and relevant policy documents. Data collection techniques are employed through systematic literature reviews, while data analysis is conducted using thematic content analysis methods. The main findings show that a budgeting model based on five stages—goal setting, needs identification, budget preparation, monitoring and evaluation, and stakeholder involvement—is able to encourage the effectiveness of fund use, strengthen public transparency, and increase community participation. In addition, the integration of digital financial technology and diversification of financing sources, including the use of waqf, are key to creating fiscal sustainability for educational institutions. This study provides theoretical contributions to Islamic education financial management and recommends further empirical studies to test the validity and applicability of the model in various institutional contexts.